Long-Term Prognostic Factors in Patients With Antineutrophil Cytoplasmic Antibody-Associated Vasculitis: A 15-Year Multicenter Retrospective Study - Liao, Qian-Qian; Ren, Ya-Fei; Zhu, Ke-Wei; Qin, Dong; Mo, Yan-Ju; Cong, Shan; Wu, Juan; Wang, Chun-Ying; Cui, Xiao-Jiao; Xu, Hong-Zhen; Guo, Lin-Zheng; Zhang, You-Yan; et al. (Frontiers in Immunology, 2022)
Background Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a multisystem autoimmune disease with small-vessel involvement. In AAV, microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA) are major clinicopathologic variants. In addition, myeloperoxidase (MPO) and proteinase 3 (PR3) are major target antigens. The objective of the study was to explore the predictive factors for long-term survival in AAV patients. Materials and Methods A multicenter retrospective study was carried out on 407 patients between 2005 and 2020. Clinical parameters were obtained from laboratory tests including the ANCA types, antinuclear antibody (ANA), extractable nuclear antigen (ENA), anti-streptolysin O (ASO), glomerular filtration rate (GFR), and the laboratory examinations for the blood routine, liver function, renal function, and immunity, etc. The data for clinical parameters were collected from electronic medical records (EMRs), and the data for patient survival were acquired through regular follow-up. The association of clinical parameters with overall survival (OS) along with 3-year and 5-year survival rates was analyzed, and the nomogram as a predictive model was established according to the analysis results. Results In the present study, 336 (82.6%) patients and 46 (11.3%) patients were diagnosed with MPA and GPA, respectively. The mean and median OS for all the patients were 2,285 and 2,290 days, respectively. The 1-year, 3-year, 5-year, and 10-year cumulative survival rates for all the patients were 84.2%, 76.3%, 57.2%, and 32.4%, respectively. Univariate and multivariate survival analyses indicated that the independent prognostic factors included age, pathological categories (MPA, GPA, and other types), serum ANCA types (negative or positive for MPO and/or PR3), ANA, ASO, GFR, lymphocyte, neutrophil-to-lymphocyte ratio (NLR), and C-reactive protein (CRP), and these clinical parameters except for ASO were used to construct a nomogram. The nomogram for 3-year and 5-year survival rates had a C-index of 0.721 (95% CI 0.676–0.766). The calibration curves showed that the predicted values of the nomogram for 3-year and 5-year survival rates were generally consistent with practical observed values, and decision curve analysis (DCA) further demonstrated the practicability and accuracy of the predictive model. Conclusion Laboratory tests at diagnosis have great significance in the prediction of long-term survival in AAV patients.